A survey of female students with migraine: what is the influence of family history and lifestyle?. (1st February 2014) - Dzoljic, Eleonora; Vlajinac, Hristina; Sipetic, Sandra; Marinkovic, Jelena; Grbatinic, Ivan; Kostic, Vladimir
<x xml:space="preserve">Abstract</x> Objectives: To compare characteristics of migraine and some lifestyle habits in migraineurs with and without a positive family history for migraine. Method: The prevalence study was combined with a case-control study and comprised 245 female students with migraine. Results: Out of 245 female students with migraine, 132 (53.9%) had a positive family history for migraine. In comparison with migraineurs who had not, those with a positive family history were younger at the onset of migraine and significantly more frequently reported menstrual migraine (p < 0.001), unilateral pain ( p < 0.05) and pulsate pain ( p < 0.05) as well as severe headache ( p < 0.01). In comparison to migraineurs with a positive family history for migraine, those who did not report a significantly higher frequency of average number of meals per day of <3 ( p < 0.001), missed meals ( p < 0.05) and an average sleep duration of ≤6 h ( p < 0.05). Conclusions: The results of the present study are in line with literature showing a high frequency of positive family history for migraine among migraineurs. They also suggest that subjects with a positive family history have a lower "migrainous threshold" for the development of migraine and that environmental factors are more important for the occurrence of migraine in subjects without a positive family history. Accordingly, the conclusions of this study are limited to reproductive aged women.